Factors affecting purchase intention of recalled halal products among Malaysian Muslim consumers - Mohd Yunus, Nurul Syuhada (2018)
Product recalls do not only lead to the damage of company image but may also cause safety and health problems to Muslim consumers. Malaysia was shaken by several cases of halal products being recalled by the Department of Islamic Development Malaysia (JAKIM) in the past few years, hence Muslim consumers have had doubt over the sanctity of the products, even after the reinstatement of halal certification of recalled products. The industries and authorities have also suffered in their image and profit because of the consumer’s suspicion and boycott. Thus, this study’s main objective was to examine the factors affecting purchase intention of recalled halal products among Malaysian Muslim consumers. The study also intended to test the mediating roles of trust between religious orientation and halal knowledge towards the purchase intention of product recalls. A quantitative survey was designed using self-administered questionnaires. A total of 279 questionnaires were collected from respondents in Kelantan, Negeri Sembilan, Selangor and Perak. They were chosen using a purposive sampling procedure where the respondents of this study were Muslim consumers who had experience in purchasing recalled halal products before this. The findings of this study revealed that attitude, subjective norms, brand image and halal knowledge significantly affects Malaysian Muslim consumers’ purchase intention of recalled halal products. On the other hand, trust mediates the relationship between halal knowledge and purchase intention of recalled halal products. However, religious orientation did not have any significant relationship in this study’s context of findings. The implications of this study were primarily beneficial and valuable to the marketers of halal products by offering an insight into the intention of consumers to purchase products that had been recalled by the authorities. In conclusion, the study proved that theory of reasoned action factors (attitude and subjective norms) are still relevant in the context of purchasing halal products that were once recalled by the authorities due to some reasons. Hence, the general findings of this study is important for manufacturers of halal products in Malaysia, whereby in the event this happens to their products, manufacturers would still be able to influence their consumers to continue purchasing their products by enhancing marketing efforts to change and leverage five factors: attitude, subjective norms, brand image, halal knowledge and trust. The findings of this study also give the academicians and researchers knowledge as a benchmark to assist them in the future.